The Effect of Coral Reef Ecological Changes on the Socio-Economic Community in Mapur Village - Adrinal, Adrinal; Wahyudin, Wahyudin; Lestari, Febrianti (Journal of Coastal and Ocean Sciences, 2024)
The condition of coral reefs is still good on Mapur Island, which benefits community activities such as fishing and marine tourism. However, continuous activities can degrade the coral reef ecosystem, so the government has made it a Marine Conservation Area for the Eastern Region of Bintan Island. This research aims to determine the ecological condition of coral reefs on Mapur Island, the influence of the coral reef ecosystem on socio-economics, as well as the impacts felt before it was designated and after it was designated as a conservation area in Mapur Village, Marine Conservation Area in the Eastern Region of Bintan Island. The results show that increasing live coral cover and decreasing dead coral cover have shown a positive recovery trend. Establishing a coral reef ecosystem conservation area in Mapur Village has several substantial impacts. Even though most people have good knowledge and perception about the function and benefits of conservation areas, primarily as fish habitats, the main challenge still lies in access to infrastructure, which is considered inadequate. The economic impact of establishing a conservation area is not yet significant because most people do not see a substantial increase in income. However, the community feels support for their livelihoods through the sustainability of fish resources. Changes in coral cover on the socio-economic conditions of the people of Mapur Island influence the ecosystem and local communities, fisheries and marine resources, the marine tourism sector of Mapur Village, natural resource management, direct economic influence, diversification of livelihoods, education, and environmental awareness, improving infrastructure and facilities, as well as challenges and limitations